2008
DOI: 10.1111/j.1365-2591.2007.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Confocal immunolocalization of VE‐cadherin‐ and CXC chemokine‐expressing endothelial cells in periapical granulomas

Abstract: VE-cadherin expression in ECs was lower than CXCL8 and CXCL10, suggesting that inflamed ECs in periapical granulomas could increase vascular permeability and that leukocyte chemotaxis mediated by ECs might occur. These findings may suggest the possibility that ECs could play a pivotal role in cell recruitment in periapical granulomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Dramatic increase in permeability and vascular fragility via administration of anti‐VE‐cadherin in mouse model was observed (Corada et al , ). The relation between VE‐cadherin and vascular permeability in inflamed endothelial cells in cell cultures (Sheets et al , ), and a loss of cell adhesion (Takeichi et al , ), the barrier breakdown and increased paracellular permeability (Shen et al , ) as a result of altered expression of VE‐cadherin were also reported in different tissues. Therefore, alterations in VE‐cadherin expression (as VEGF expression) may be an important stage in the initiation and progression of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Dramatic increase in permeability and vascular fragility via administration of anti‐VE‐cadherin in mouse model was observed (Corada et al , ). The relation between VE‐cadherin and vascular permeability in inflamed endothelial cells in cell cultures (Sheets et al , ), and a loss of cell adhesion (Takeichi et al , ), the barrier breakdown and increased paracellular permeability (Shen et al , ) as a result of altered expression of VE‐cadherin were also reported in different tissues. Therefore, alterations in VE‐cadherin expression (as VEGF expression) may be an important stage in the initiation and progression of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Dual‐colour immunofluorescence imaging was used to identify cell proliferation associated with SIRT1 expression, as previously described (Takeichi et al . ). In brief, frozen tissue sections of periapical granulomas or healthy gingival tissues were treated with 10% (v/v) normal goat serum (Vector Laboratories, Burlingame, CA, USA) for 60 min to block nonspecific binding and incubated with a rabbit monoclonal anti‐human SIRT1 antibody (1/100; Abcam, Cambridge, UK) or a mouse monoclonal anti‐human Ki‐67 antibody (1/100; Abcam) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 97%
“…Analysis of the chemokines KC/CXCL1 (the analogue of the human CXCL8), in an experimental model of PD in mice, revealed their expression in diseased tissues, preferentially in the junctional epithelium, and their correlation with the migration of PMNs . Furthermore, there was a significant increase in the expression of CXCL8 by epithelial cells from periapical granulomas, suggesting that those cells also could increase vascular permeability and leukocyte chemotaxis (Takeichi et al, 2008).…”
Section: Chemokines As Determinants Of Host Response Naturementioning
confidence: 96%